GENETIC AND BIOLOGICAL INSIGHTS INTO NEUROANESTHESIA: IMPLICATIONS FOR ANESTHETIC SAFETY AND THERAPEUTIC INTERVENTIONS IN PATIENTS WITH PRE-EXISTING CEREBRAL INJURY - Silva, Beatriz Viana Souto da; Vasconcelos, Elena Antunes de; Pádua, Ana Carolina Diniz e; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Neuroanesthesia in patients with pre-existing cerebral injury presents unique challenges and potential complications. These challenges underscore the importance of recent advancements in genetic and biological research, which have provided valuable insights into the complex interplay between anesthetics, genomic expression, epigenetic modifications, and molecular mechanisms that contribute to anesthesia-induced neurotoxicity and adverse neurocognitive outcomes. This narrative review explores the current knowledge regarding the genetic and biological factors influencing neuroanesthesia, focusing on patients with pre-existing cerebral injury. By synthesizing findings from preclinical and clinical studies, this review aims to elucidate the mechanisms underlying anesthetic-induced neurodegeneration, genetic predisposition to anesthetic complications, and potential therapeutic interventions to mitigate adverse effects. The implications of these insights for developing safer anesthetic practices and personalized approaches to neuroanesthesia are discussed. Understanding the genetic and biological underpinnings of neuroanesthesia is crucial for optimizing patient care and outcomes in the context of pre-existing cerebral injury.